PERANCANGAN PUSAT KULINER JAWA TENGAH DI KABUPATEN BOYOLALI DENGAN ARSITEKTUR METAFORA - Sukma Amirul Purwanto; Anggraeni Dyah Sulistiowati; Sri Kurniasih (MAESTRO, 2023)
Culinary in Indonesia is a form of tourism that must be developed and maintained so that its sustainability is maintained. Boyolali is a district located in the province of Central Java which has great agricultural and animal husbandry potential to support the culinary tourism sector. If the agricultural and plantation potential in Boyolali Regency is utilized so that it has a culinary tourism sector which contains dishes from several typical Central Javanese foods. It is hoped that the culinary center in Boyolali Regency will become a new tourism icon and make local and foreign tourists interested in visiting Boyolali Regency. A culinary center that accommodates several types of typical Central Javanese cuisine and has supporting facilities such as a playground, theater room, multi-purpose building, photo spots, various souvenirs and agro-tourism. By applying the metaphorical architectural theme at the Boyolali Regency Culinary Center it is hoped that it will attract tourists to come and be able to fulfill the space requirements and functions of the activity itself.